Formazione, aggiornamento ed accreditamento in Medicina del Lavoro: il contributo della Società Italiana di Medicina del Lavoro e Igiene Industriale (SIMLII) nel primo decennio del 2000 / Permanent education, updating and accreditation in Occupational Medicine: the contribution of the Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII) in the first decade of the 21st century - Abbritti, G.; Bertazzi, P.A.; Murgia et al., N. (La Medicina del Lavoro, 2011)
«Permanent education, updating and accreditation in Occupational Medicine: the contribution of the Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII) in the first decade of the 21st century». Background. Permanent education of health workers is obligatory under Italian legislation and is managed by the Ministry of Health through its Permanent Education Programme. Methods. In 2000 the Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII), set up and implemented a programme of Permanent Education and Accreditation for specialists in occupational medicine, based on participation in “non-mandatory” and “mandatory” educational activities. “Non-mandatory” activities were chosen by the individual physician for education in topics related to occupational medicine. “Mandatory” educational activities, which were organised by the Society, included in-depth analysis of the Society’s guidelines related to specific topics in occupational medicine. Results and Discussion. The Guidelines study course played a pre-eminent role in the Society’s permanent education programme and was greatly appreciated by all participants. The Board of the Society has recently approved a new Plan of Permanent Education, identifying the means (Guidelines, Consensus Documents) whereby occupational physicians can improve their professional standards. The Plan’s aims are to facilitate accreditation and also to identify and promote high-quality updating programmes which will lead to recognition of “professional excellence”. Crucial to its success will be a 3-year on-line learning programme (MeLA) that SIMLII has just implemented, which will enable occupational physicians to acquire credits in “Occupational Medicine and Workplace Safety”, as required by current Italian legislation. This article summarizes SIMLII activities over the past ten years in the field of permanent medical education for occupational physicians.